Penerapan Biaya Kualitas dalam Meningkatkan Profitabilitas pada A&B Cake& Bakery di Kabupaten Banyuwangi - Nabila Agustina Rais; Yulinartati Yulinartati; Ibna Kamelia Fiel Afroh (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Good product quality can support the sustainability of a business. So there are quality costs for the company in providing good quality to consumers so that they do not switch to competitors. Quality costs can increase profits if there are cost suppressors and proper cost utilization. The aim of this research is to apply quality costs to A&B Cake & Bakery to determine the role of quality costs in increasing profitability. The method used is descriptive qualitative. The research results show that control costs (prevention costs) are lower than failure costs (internal failure costs and external failure costs), but this does not affect the company in the short term because the sales side is high so it helps in obtaining profits but is not yet maximized. This is not good for the company in the long term because it can affect the company's development. To achieve maximum profits, managers must change the company's strategy. Such as utilizing costs by adding appraisal costs, this is very necessary for companies due to the large number of defective products, if these costs are added then failure costs will decrease and the company can achieve its goal, namely achieving maximum profits. Keywords: Cost of Quality, Profitability